Dokapitalizacija brez emisijskega zneska - Drnovšek, Gregor (Podjetje in delo, 2016)
The general meeting resolution on ordinary share capital increase usually contains data on the basis of which the issue price of shares is at least identifiable. Permissibility of only identifiable issue price of shares was finally clarified by the amendment ZGD-1I which modified the second paragraph of Article 337 of the ZGD-1. This article however focuses on circumstances when the resolution on ordinary share capital increase does not contain any data on the issue price of shares. Author represents a standpoint under which such resolution is valid and at the same time clarifies, whether management has to issue the shares at par or above par.
Keywords: delniške družbe; kapital; kapitalska razmerja